Dynamics of Gastrointestinal Activity and Ruminal Absorption of the Methane-Inhibitor, Nitroethane, in Cattle - Božic, Aleksandar K.; Gutiérrez-Bañuelos, Hector; Corral-Luna, Agustin; Carstens, Gordon; Arévalos-Sánchez, Martha María; Félix-Portillo, Monserrath; Muro-Reyes, Alberto; Arzola-Álvarez, Claudio; Anderson, Robin C.; Harvey, Roger B. (Frontiers in Veterinary Science, 2022)
Ruminal methane production represents a digestive inefficiency for the host, resulting in losses of up to 12% of the gross energy consumed by the animal and contributes nearly 27% of the total United States’ emissions of this potent greenhouse gas. Nitroethane is a potent methane-inhibitor for ruminants but little is known regarding simultaneous effects of repeated administration on pre- and post-gastric methane-producing activity and potential absorption and systemic accumulation of nitroethane in ruminants. Intraruminal administration of 120 mg nitroethane/kg body weight to Holstein cows over a 4-day period transiently reduced (P < 0.05) ruminal methane-producing activity as much as 3.6-fold while concomitantly increasing (P < 0.05) fecal-methane producing activity by as much as 8.8-fold when compared to pre-treatment measurements. These observations suggest a bacteriostatic effect of nitroethane on ruminal methanogen populations resulting in increased passage of viable methanogens to the lower bovine gut. Ruminal VFA concentrations were also transiently affected by nitroethane administration (P < 0.05) reflecting adaptive changes in the rumen microbial populations. Mean (± SD) nitroethane concentrations in plasma of feedlot steers administered 80 or 160 mg nitroethane/kg body weight over a 7-day period were 0.12 ± 0.1 and 0.41 ± 0.1 μmol/mL 8 hours after the initial administration indicating rapid absorption of nitroethane, with concentrations peaking 1 day after initiation of the 80 or 160 mg nitroethane/kg body weight per day treatments (0.38 ± 0.1 and 1.14 ± 0.1 μmol/mL, respectively). Plasma nitroethane concentrations declined thereafter to 0.25 ± 0.1 and 0.78 ± 0.3 and to 0.18 ± 0.1 and 0.44 ± 0.3 μmol/mL on days 2 and 7 for the 80 or 160 mg nitroethane/kg body weight per day treatment groups, respectively, indicating decreased absorption due to increased ruminal nitroethane degradation or to more rapid excretion of the compound. These results provide important information regarding effects of nitroethane administration to cattle and are consistent with ruminal in situ enrichment of nitroethane-degrading bacteria.